2017
DOI: 10.1515/cpe-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of momentum transfer processes in a mechanically agitated air – biophase – liquid system

Abstract: The results of numerical computations concerning momentum transfer processes in an air -biophase -liquid system agitated in a bioreactor equipped with baffles and a Smith turbine (CD 6 impeller) are presented in this paper. The effect of sucrose concentration on the distributions of the velocity of the continuous phase, gas hold-up and the size of gas bubbles in the system was analysed. Simulation results were presented in the form of the contours of the analysed magnitudes. The effect of sucrose concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the case of modeling the hydrodynamics of the gas-liquid system, characterized by a relatively high proportion of the dispersed phase (gas phase), the two-phase model is often used as a model in which both phases are treated as two interpenetrating continuums (Euler-Euler approach) (Kerdouss et al 2008;Jaworski 2005;Joshi et al 2011;Kaiser et al 2011;Knopkar and Ranade 2006). To obtain better agreement between the data obtained as a result of simulations and experimental data, the computational fluid dynamics (CFD) method is combined with the population balance method (PBM) (Gimbun et al 2009; Ranganathan and Sivaraman 2011; Musiał et al 2014Musiał et al , 2017. Based on the results of numerical simulations of hydrodynamics of multiphase systems, a number of information on the distribution of liquid and gas velocities, local values of gas hold-up and distributions of kinetic energy of turbulence and its dissipation in a stirred tank can be obtained (Oniscu et al 2002;Vrábel et al 2000;Delafosse et al 2014;Gelves et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of modeling the hydrodynamics of the gas-liquid system, characterized by a relatively high proportion of the dispersed phase (gas phase), the two-phase model is often used as a model in which both phases are treated as two interpenetrating continuums (Euler-Euler approach) (Kerdouss et al 2008;Jaworski 2005;Joshi et al 2011;Kaiser et al 2011;Knopkar and Ranade 2006). To obtain better agreement between the data obtained as a result of simulations and experimental data, the computational fluid dynamics (CFD) method is combined with the population balance method (PBM) (Gimbun et al 2009; Ranganathan and Sivaraman 2011; Musiał et al 2014Musiał et al , 2017. Based on the results of numerical simulations of hydrodynamics of multiphase systems, a number of information on the distribution of liquid and gas velocities, local values of gas hold-up and distributions of kinetic energy of turbulence and its dissipation in a stirred tank can be obtained (Oniscu et al 2002;Vrábel et al 2000;Delafosse et al 2014;Gelves et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the obtained simulations, they found that hydrodynamic interactions between the curved stirrer blades and mixing tank baffles are responsible for disturbing the symmetry of the fluid flow in the axial and radial planes of the stirrer tank. Numerical analysis of the impact of sucrose concentration on the distribution of continuous phase velocity, share of gas hold-up and size of gas bubbles was the subject of research by Musiał et al (2017). Based on the conducted simulations, they found that the local liquid velocity values decrease with the increase in sucrose concentration in the system, while the distributions of gas hold-up and the size of gas bubbles to a small extent depend on sucrose concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental models to describe the flotation process, particularly related to the collection zone in terms of hydrodynamic conditions inside the flotation chamber have been developed for many years; however, still, a number of crucial unsolved issues is very large [138][139][140]. A general flotation model presents creation [141,142] or disintegration [143,144] of flotation aggregates (bubble-particle) and analyses of the phase particles interaction within a turbulent environment [119,120].…”
Section: Particle In Three-phase Reactors Drawdown Of Floatingmentioning
confidence: 99%